La terminología jurídica en la literatura francesa - Aguilar Camacho, María del Carmen (Anales de Filología Francesa, 2010)
This work tries to analyze the influence that historic and legal juncture has over Literature. Such influence becomes evident if we focus ourselves on two different aspects: first, the interest that the legal world has in literature and which is apparent in some French literary works, either fiction or real, which deals the legal themes and where we find its subsequent specific terminology; second, the interest of the government’s authority for controlling the style and the fond of every written text independently of its nature, ordering a severe control over the literary production. So, the work is based on the analysis of both, a several literary French works and the most relevant rules on literary documents.